DETERMINAN PROFITABILITAS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2025 - Alya Mustika; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2026)
Profitability is an important indicator used to assess a company's financial performance because it reflects the company's ability to generate profits effectively and sustain its business operations. Various internal factors may influence profitability, including leverage, liquidity, operational efficiency, capital intensity, sales growth, and firm size. This study aims to examine the effects of these factors on profitability in consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2025 period.This study employs a quantitative approach using secondary data obtained from the annual reports of consumer non-cyclicals companies listed on the Indonesia Stock Exchange. The sample consists of 46 companies selected through purposive sampling. Data were analyzed using multiple linear regression, supported by descriptive statistical analysis and classical assumption tests.The results show that leverage has a significant negative effect on profitability. In contrast, operational efficiency, sales growth, and firm size have significant positive effects on profitability. Meanwhile, liquidity and capital intensity do not significantly affect profitability. These findings indicate that effective debt management, improved operational efficiency, and firm growth are important factors in enhancing profitability in the consumer non-cyclicals sector.